Water flowing under the law - Laster R.; Gat J.; Livney D. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
Like a bridge over troubled waters, the law can act to soothe disputes over water use. That, in fact, is the genius of the law in democratic countries. Water law is that compendium of rules that protects natural resources as it provides man with a life force. When used wisely, water law can be a tool for understanding and well being; when ignored, a blunt instrument of deprivation.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)